Diagnostic accuracy of fine needle aspiration cytology in comparison to open biopsy for lesions of oral cavity in Covid-19 era - Syed Shumail Ahmad; Gulraiz Zulfiqar; Muhammad Imran (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the diagnostic accuracy and uses of fine needle aspiration cytology with histopathology in the diagnosis of lesions of oral cavity. Method: The single-centre, prospective, non-randomised controlled trial was conducted at the departments of Oral and Maxillofacial Surgery and Pathology of Allama Iqbal Medical College/Jinnah Hospital, Lahore, Pakistan, from January 10 to August 10, 2021, and comprised patients of either gender aged >10 years having superficial or deep well-established mass, palpable, nodular, ulcerative lesions, swellings of the oral cavity or of major or minor salivary glands having intraoral presence or manifestation with size >1cm. Data was analysed using SPSS 20. Results: Of the 43 patients, 22(51.2%) were males and 21(48.8%) were females. The overall mean age was 40.5+/-15 years (rang: 13-70 years). On cytological examination, 6(14%) samples were excluded for being insufficient aspirate. Of the remaining 37(86%) samples, 20(51.4%) were detected with malignancy on histopathology. The accuracy of fine needle aspiration cytology was 33(89.19%). Conclusion: Fine needle aspiration was found to be a reliable and cost-effective technique in the diagnosis of oral cavity lesions. Key Words: Carcinoma, Squamous cell, Fine-needle, COVID-19, Minimally invasive surgical procedures, Mouth neoplasms.